Analis Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas pada Lembaga Pendidikan (Studi Kasus Madrasah Aliyah Negeri 1 Malang) - Muhammad Hatta Bahdiar; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The use of cash in madrasah operations is very easy to be misappropriated or misused. The occurrence of fraud needs to be prevented by having a system that supports cash transactions. The purpose of this study was to analyze the effectiveness of the accounting information system for cash receipts and disbursements at MAN 1 Malang.The researcher used a qualitative descriptive method to determine the effectiveness of the accounting information system on cash receipts and disbursements at Madrasahs which included cash receipts and disbursements at Madrasah Aliyah Negeri (MAN) 1 Malang. This study uses internal data. The collection technique uses documentation and interviews. The steps of data analysis in this research are: (1) reducing data (data reduction), (2) presenting data (data display), (3) drawing conclusions (conclusion drawing).The results showed that the accounting information system at MAN 1 Malang using the JIBAS application was considered effective and provided many conveniences for the madrasa in terms of cash receipts and disbursements. Cash receipts with the JIBAS application begin with an accounting account code, then enter the types of receipts, after that enter receipt transactions for the current financial year, this receipt produces cash receipts reports in the form of: payment reports per class, payments per student, student payments in arrears, payment per group of prospective students, payment per prospective student, payment of prospective students who are in arrears, recapitulation of receipts, recapitulation of student arrears, cash receipts and receipts journal.In terms of cash disbursements, the use of the JIBAS accounting information system is also considered effective. Cash disbursement at MAN 1 Malang starts from the accounting account code and then the types of expenses and continues with expense transactions consisting of: expense transactions, search for expense data and expense journals.Keywords: Accounting information system, revenue, expenditure.